Estilos parentais de origem, apego e características de personalidade de mulheres que passaram por violência conjugal - Barbosa, Thamires Pereira (2019)
Nowadays, violence against women is considered a public health issue, which often goes through generations. Therefore, studies are needed to better understand developmental and generational factors among women victims of conjugal violence. Therefore, this study aimed to evaluate the parenting styles of origin, attachment types and the personality of women victims of conjugal violence. Parental styles were investigated through the Parenting Styles Inventory (IEP) and attachment types through the Relationship Structures questionnaire (ECR-RS). The personality traits were investigated through the NEO-FFI-R instrument (reduced version of NEO-PI-R), in order to explore possible relations between the attachment types and the personality of the participants. The results show that participants presented mostly risk parental practices (by their parents), and also secure attachments in the differents relational figures, except to the boyfriend figure. In addition, a negative correlation was found between agreeableness and global insecure attachment, and an association between neuroticism and attachment types in dating. The present study emphasizes the importance of investigate aspects of the family of origin that can act as risk or protection factors in situations of conjugal violence.